ANALYSIS OF GENETIC STABILITY OF MICROPROPAGATED SUGARCANE IN DIFFERENT SUBCULTURE FREQUENCIES USING SSR MARKER - Alfia Annur Aini Azizi; Ika Roostika; Reflinur Reflinur; Darda Efendi (Pusat Penelitian dan Pengembangan Perkebunan, 2020)
In vitro technique is an effective method to produce high quality and uniform sugarcane seedlings. This study was aimed to determine genetic stability based on SSR marker analysis of six varieties of sugarcane subcultured in regeneration media. It was conducted at the ICABIOGRAD Molecular Biology Laboratory, Bogor, from May 2015 to October 2016. Six sugarcane varieties (PS 862, PS 865, PS 881, PSJK 922, TK 386, and GMP 3) derived from apical shoot explants were subcultured on MS regeneration media enriched with 0.3 mg/l BAP; 0.5 mg/l IBA; and 100 mg/l PVP, for 3, 6 and 9 times. Sugarcane DNA was extracted using the CTAB method; then, the genetic stability was analyzed using 20 pairs of SSR primers. Data were analyzed in groups using the UPGMA method in the SAHN subprogram available on NTSYS software. The results showed that five sugarcane varieties (PS 865, PS 881, PSJK 922, TK 386, and GMP 3) subcultured up to nine times on the regeneration media remained genetically stable with similarity coefficient to their mother plants value more than 0.94. However, PS 862 variety had genetically unstable after the sixth and the ninth subcultures, the similarity coefficient value to its mother plant was only 0.64, indicated that it experienced somaclonal variations. The study concluded that the in vitro shoots of the other varieties were more genetically stable during subcultures compared to PS 862 sugarcane variety based on SSR marker analysis. Further study is needed to find out the cause of genetic changes in PS 862.Keywords: Saccharum officinarum, apical shoots, in vitro propagation.